If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -42 = 6x + 6x + -6 Reorder the terms: -42 = -6 + 6x + 6x Combine like terms: 6x + 6x = 12x -42 = -6 + 12x Solving -42 = -6 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -42 + -12x = -6 + 12x + -12x Combine like terms: 12x + -12x = 0 -42 + -12x = -6 + 0 -42 + -12x = -6 Add '42' to each side of the equation. -42 + 42 + -12x = -6 + 42 Combine like terms: -42 + 42 = 0 0 + -12x = -6 + 42 -12x = -6 + 42 Combine like terms: -6 + 42 = 36 -12x = 36 Divide each side by '-12'. x = -3 Simplifying x = -3
| 11=-15x-7 | | 40=(24/4)h | | 4-6m=-2 | | 6[3-(-4x-3)]=72x+108 | | 4x+3=2-8x | | -36t=-8 | | 5b-4=-8 | | 4/12x5/6 | | 36=12b | | 6x+7=-17+2x | | 3(4y-1)-2=8-8.5 | | -1/12x | | .333-.666=1 | | 5/13-2x=(-8/13) | | 2.1x-13.79=4.9 | | .009=0.01 | | -8a^2+72=0 | | .333-.666= | | 5y-2=-6 | | y-(-8)=(4/5)(x-3) | | x+9=41-7x | | x+3x+3x=12 | | 2x-6=8x+5 | | 8d+10=6 | | 18.7n=-26.18 | | 8+6x=-x+78 | | 2x-8=7x+8 | | 19000=-125(t-122) | | -5(3x-5)=-140 | | 6x=-14x^2 | | t+2t=2700 | | 5x+7-4x=7+2x-6 |